Hubungan Derajat Keparahan Gejala dengan Kualitas Tidur Pasien Penyakit Paru Obstruktif Kronik (PPOK) di RSUD Abdul Moeloek Provinsi Lampung - Ayu Dinda Fatimah; Iswandi Darwis; Agustyas Tjiptaningrum; Khairun Nisa Berawi (Majority, 2022)
Chronic Obstructive Pulmonary Disease is a disease that has a high prevalence. The prevalence of COPD is always increasing in every country in the world. Deaths of people with COPD are associated with an increase in the severity of symptoms of the disease. The symptoms of COPD continue to worsen and have an impact on the decline in sleep quality of COPD patients. The Lampung Provincial Government makes COPD as one of the threats in carrying out health development in Lampung Province in 2015 to 2019. The purpose of this study was to determine the relationship relationship between severity of symptoms and sleep quality of patients with Chronic Obstructive Pulmonary Disease (COPD) in Abdul Moeloek regional hospital Lampung Province. It is used observational analytical method with cross sectional design was registered in this research. The sample was 40 COPD patients in Abdul Moeloek Regional Hospital Lampung Province, taken by consecutive sampling method. The study was conducted using the COPD Assessment Test questionnaire and Pittsburgh Sleep Quality Index questionnaire in the hospital, patient’s house, or patient’s office. Then the results of this study were processed using computer software. Result of analysis with Chi Square test with 95% confidence level (α = 0,05) showed p value 0,01 < 0,05. There is a significant association of Severity of Symptoms and Sleep Quality of Patients with Chronic Obstructive Pulmonary Disease (COPD) in Abdul Moeloek Regional Hospital Lampung Province.